1992
DOI: 10.1159/000247399
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Onychomycosis during the Treatment with Bifonazole/Urea Ointment

Abstract: In the present study, we investigated the effects of bifonazole/urea ointment, a novel topical drug for the treatment of onychomycosis, on the ultrastructure of normal and fungus-infected human toenails by scanning electron microscopy. Nails were treated with the drug ex vivo and compared to untreated controls. During treatment, the corneocyte layers disintegrated, and the structure markedly loosened. After 5 days of treatment, the morphology of fungal cells, found at the undersurface of infected nails, was ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The application of urea, through hydration of the nail plate, causes visible changes. An ultrastructural study of the effects of 40% urea showed that there was considerable disruption of the cell/cell adhesion of corneocytes in the nail plate 19 accounting for visible urea‐associated nail plate change. Therefore, in judging clinical response, the visual appearance of the nail bed after therapy involving urea cannot be rated as ‘normal’ until the morphological changes due to nail plate ablation have faded.…”
Section: Discussionmentioning
confidence: 99%
“…The application of urea, through hydration of the nail plate, causes visible changes. An ultrastructural study of the effects of 40% urea showed that there was considerable disruption of the cell/cell adhesion of corneocytes in the nail plate 19 accounting for visible urea‐associated nail plate change. Therefore, in judging clinical response, the visual appearance of the nail bed after therapy involving urea cannot be rated as ‘normal’ until the morphological changes due to nail plate ablation have faded.…”
Section: Discussionmentioning
confidence: 99%
“…Several such micrographs were used in the present study. It is known that the surfaces of normal nails present a squamous polygonal appearance with well-defined intercellular boundaries [6,13].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…[27][28][29][30][31] One of the most widely used antifungal-urea combinations evaluated in several small-scale trials is 1% bifonazole in combination with 40% urea ointment. [27][28][29][30][31] One of the most widely used antifungal-urea combinations evaluated in several small-scale trials is 1% bifonazole in combination with 40% urea ointment.…”
Section: Topical Antifungal Agentsmentioning
confidence: 99%